Science, Technology and Innovation: The Importance of Multi-Media in Academic Libraries - Usman, Abubakar N. (Lapai Journal of Economics, 2020)
In the present academic and special library setting the educational videos, instructional visual aids and audio learning resources form a significant collection. Time is fast catching up the world over that the traditional forms of collection development techniques and collection maintenance strategies need replacements with the upcoming trends in the profession. Connoting the essence of libraries as a collection of sources of information and similar resources, selected by experts and made accessible to a defined community for reference or borrowing, often in a quiet environment conducive for study. The study discuss briefly main elements of multi-media, types, methods of presentation, types of software, access methods and its advantages in academic libraries.